2011
DOI: 10.1103/physrevb.83.125419
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational instabilities in resonant electron transport through single-molecule junctions

Abstract: We analyze various limits of vibrationally coupled resonant electron transport in single-molecule junctions. Based on a master equation approach, we discuss analytic and numerical results for junctions under a high bias voltage or weak electronic-vibrational coupling. It is shown that in these limits the vibrational excitation of the molecular bridge increases indefinitely, i.e. the junction exhibits a vibrational instability. Moreover, our analysis provides analytic results for the vibrational distribution fu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
289
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(296 citation statements)
references
References 82 publications
7
289
0
Order By: Relevance
“…43,[50][51][52] Moreover, the non-equilibrium phonon distribution itself has been found to possess non-trivial properties. 51,[53][54][55][56] These results clearly promotes investigations of electron-photon analogs of electron-phonon phenomena, performed in strongly coupled conductor-cavity systems.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…43,[50][51][52] Moreover, the non-equilibrium phonon distribution itself has been found to possess non-trivial properties. 51,[53][54][55][56] These results clearly promotes investigations of electron-photon analogs of electron-phonon phenomena, performed in strongly coupled conductor-cavity systems.…”
Section: Introductionmentioning
confidence: 85%
“…(30), the photon distribution and hence the population is not convergent for charge degeneracy, ∆E C = 0, in the limit of couplings, λ 1 ≪ 1, for voltages above the first onset of photon emission. 51,55 This is because the rate for going from a state with n to a state with n + 1 photons is equal to the rate for the opposite process, which gives an equal probability of all photon states. In metallic dot the processes n + 1 → n has larger rate than n → n + 1, as discussed in detail in Appendix C.…”
Section: A Single-modementioning
confidence: 99%
“…If one also takes |J| = 1 2 |U ′ − U| to be small, then the low-lying molecular states will contain only a weak admixture of components havingn b > 0, where (as before)n b is the number operator for the transformed boson mode defined in Eq. (32). Under this simplifying assumption (which we re-examine in Sec.…”
Section: Isolated Moleculementioning
confidence: 99%
“…[28][29][30] Single-molecule junctions therefore provide a valuable opportunity to study charge transfer in systems with strong competing interactions. 31,32 It has recently been demonstrated that the energies of the molecular orbitals in a single-molecule junction can be tuned relative to the Fermi energy of the electrodes by varying the voltage applied to a capacitively coupled gate. 33 Similar control has for some time been available in another class of nanoelectronic device: a quantum dot coupled to a twodimensional electron gas.…”
Section: Introductionmentioning
confidence: 99%
“…None of these couplings are assumed to be weak. Computationally, the exact master equation may be useful for the testing of various approximations (e.g., weak system-bath coupling, or weak electron-vibrational coupling, or weak inter-monomer coupling) which are frequently employed in theories of quantum transport [4,[24][25][26][27][29][30][31].…”
Section: Introductionmentioning
confidence: 99%